Irrational thoughts of the translator’s personality in assessing the quality of translation - Jabbar Frayyeh Shraida; Muthana Hameed Khalaf (Institute of Advanced Engineering and Science, 2020)
The correlation between translation as an objective field and psychological characteristics has produced various psychological and translational interrogations. To investigate the role of the translator’s personality in identifying the level of irrationality beliefs, university instructors are the corpus of the present study. After using statistical means SPSS, the results of instructors of males and females were observed to advocate for an active role of the translator in some instances. The present study employed a questionnaire that is consisted of thirty-five paragraphs measures the individual's attitude towards himself and his or her family that behaves irrationally in the performance and functions. Through the results of this study, which this study found that irrational thoughts are widespread among male and female teachers. This research also provided details of making an empirical contribution to the research in translation. Thus, the seriousness of irrational thoughts, as it is one of the reasons for the incompatibility and its seriousness on translation. This led to the weakness of the translation process, which caused the distraction of the mind to broadcast the hostile rumour that managed to exploit confusion in the translation.